Obesity induces upregulation of genes involved in myocardial Ca2+ handling - Lima-Leopoldo, A. P. [UNESP]; Sugizaki, M. M. [UNESP]; Leopoldo, A. S. [UNESP]; Carvalho, R. F. [UNESP]; Nogueira, Célia Regina [UNESP]; Nascimento, A. F. [UNESP]; Martinez, P. F. [UNESP]; Luvizotto, R. A. M. [UNESP]; Padovani, Carlos Roberto [UNESP]; Cicogna, Antonio Carlos [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2008)
Obesity is a complex multifactorial disorder that is often associated with cardiovascular diseases. Research on experimental models has suggested that cardiac dysfunction in obesity might be related to alterations in myocardial intracellular calcium (Ca2+) handling. However, information about the expression of Ca2+-related genes that lead to this abnormality is scarce. We evaluated the effects of obesity induced by a high-fat diet in the expression of Ca2+-related genes, focusing the L-type Ca2+ channel (Cacna1c), sarcolemmal Na+/Ca2+ exchanger (NCX), sarcoplasmic reticulum Ca2+ ATPase (SERCA2a), ryanodine receptor (RyR2), and phospholamban (PLB) mRNA in rat myocardium. Male 30-day-old Wistar rats were fed a standard (control) or high-fat diet (obese) for 15 weeks. Obesity was defined as increased percent of body fat in carcass. The mRNA expression of Ca2+-related genes in the left ventricle was measured by RT-PCR. Compared with control rats, the obese rats had increased percent of body fat, area under the curve for glucose, and leptin and insulin plasma concentrations. Obesity also caused an increase in the levels of SERCA2a, RyR2 and PLB mRNA (P < 0.05) but did not modify the mRNA levels of Cacna1c and NCX. These findings show that obesity induced by high-fat diet causes cardiac upregulation of Ca2+ transport_related genes in the sarcoplasmic reticulum.
Keywords: Obesity; High-fat diet; Rat heart; Ca2+ cycling; mRNA; Ca2+-related genes